Tradisi Seren Taun di Kasepuhan Citorek Lebak Banten (Studi Living Hadis) - Kurniawan, Rio; Al-Faqih, Ahmad Hizazih; Hanif, Muhammad Fadli; Badrudin, Badrudin; Alif, Muhammad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The Seren Taun tradition in Citorek Village, Lebak Regency, Banten, is a ritual of gratitude for the rice harvest which is carried out every year. In the context of Indonesian agriculture, this tradition reflects the close relationship between society and nature as well as the values ​​of togetherness and religiosity. This study aims to explore the implementation and meaning of the Seren Taun tradition, as well as the social and cultural values ​​contained therein. With a qualitative approach through interviews and observations, this study explores how the Citorek community inherits this tradition and relates it to Islamic teachings. The results of the study show that Seren Taun is not only a ritual, but also a means of spiritual communication and strengthening the cultural identity of the community. This tradition is expected to continue to be preserved as a valuable cultural heritage in Indonesia.